Desain Antena Mikrostrip Double Triangular Patch dengan Slot Y untuk Aplikasi Penguat Sinyal 4G pada Frekuensi 1800 MHz - Yenniwarti Rafsyam; Alica Dewanti; Shita Fitria Nurjihan (Spektral, 2021)
Long Term Evolution (LTE) is 4th generation (4G) technology that used as cellular technology. LTE works in various bands, one of band is 1800 MHz. At each location, the signal level that will received by the user varies depending on the usage location. At indoor location, signal level will weaken due to passing the obstacle like trees or walls, so the signal level that the user receivers is less than the maximum. To improve this condition, a repeater is needed. A repeater need an antenna as a signal receiver that transmitted from eNodeB and an antenna for transmitting a signal that has been amplified. In this paper will be explained about design an antenna microstrip double triangular patch with slot Y as an indoor antenna that used for transmitting a signal that works at frequency 1800 MHz. Micostrip antenna that was fabricated and tested has specification value is obtained which are return loss = - 20,702 dB, VSWR = 1,1566, gain = 6,9 dB, and the radiation pattern is unidirectional. Signal level antenna testing is performed on three location by using four provider. The highest signal level gained by Telkomsel provider that is -77 dBm and the lowest is XL provider that is -100,6 dBm.   Keywords : 4G, antenna, frequency 1800 MHz, microstrip, patch double triangular, signal level